Survival rate and prognostic factors in advanced cervical cancer patients accompanied by renal impairment (Faculty of Medicine Universitas Indonesia, 2005)
The objective of this study was to obtain information on the survival rate of advanced cervical cancer patients with renal impairment (ACCRI) and its prognostic factors. In addition, it is hoped that by this method the scoring system for predicting the death of ACCRI patients hopetully could be obtained. Design of the study used was retrospective cohort study. Data collected were retrieved from medical records of ACCRI patients from 1 January 1998 to 31 December 2003 at Dr. Cipto Mangunkusumo National Central General Hospital, Jakarta, with a total sample of 70 cases. The results of the study showed that mean survival of all ACCRI patients was 8.2 months, mean survival at sixth month was 39%, and mean survival at one year was 3.2%. Median survival was 5.3 months. Prognostic factors affecting the survival of ACCRI patients included histopathological type (adenosquamous cell and cell differentiation), cortical thickness of the kidney less than 1 cm, and nephrostomy. (Med J Indones 2005; 14: 173-8)